PENGARUH TINGKAT PEMAHAMAN DAN TINGKAT KESADARAN WAJIB PAJAK TERHADAP KEMAUAN WP OP UNTUK MEMENUHI KEWAJIBAN PAJAK PENGHASILAN - Gati Astikawati (Jurnal Ilmiah Mahasiswa FEB, 2013)
This research has a goal to see more about the effects of personal tax payer internal factors for their wants to fulfill duty salary tax with quantitative research method. Tax is one of national income that used to build the better state/country. But in case, the tax payer desire to fulfill their salary tax One of the biggest effects comes from the tax payer personally (internal factor). Based on this personal tax payer internal factor research (understanding level and awarness level) has the significant positive effect for the tax payer desire to fulfill their duty of salary tax. Understanding level from this research absolutel has effect for the tax payer desire to fulfill their duty of salary tax. Tax payer whos have aware has significant effect to fulfill their duty of salary tax. This personal tax payer internal factors are the situations that come from them personally. This research results expected can be used to decide the strategy that will be choosen to rise up the personal tax payer desire and fulfill their salary tax. Keywords: Taxpayer, Education level, Understanding level, awarness level, income level, encouragement level